Constructing Isosurfaces with Sharp Edges and Corners using Cube Merging - Bhattacharya, A.; Wenger, R. (Computer graphics forum, 2013)
A number of papers present algorithms to construct isosurfaces with sharp edges and corners from hermite data, i.e. the exact surface normals at the exact intersection of the surface and grid edges. We discuss some fundamental problems with the previous algorithms and describe a new approach, based on merging grid cubes near sharp edges, that produces significantly better results. Our algorithm requires only gradients at the grid vertices, not at each surface‐edge intersection point. We also give a method for measuring the correctness of the resulting sharp edges and corners in the isosurface.